Nightmare Rescripting: Using Imagery Techniques to Treat Sleep Disturbances in Post-traumatic Stress Disorder - Albanese, Marzia; Liotti, Marianna; Cornacchia, Lucia; Mancini, Francesco (Frontiers in Psychiatry, 2022)
Besides affecting 8% of the general population, nightmares are one of the most frequent symptoms of traumatized individuals. This can be a significant factor in the treatment of post-traumatic disorders; indeed, several studies demonstrated its strong predictive and prognostic value. Sleep disorders, nightmares in particular, could be very distressing for individuals and need targeted interventions, especially if they are associated with a PTSD diagnosis. To date, the best technique for the treatment of traumatic sleep disturbances seems to be Imagery Rehearsal Therapy (IRT), an empirically supported method. Through a review of the literature on this matter, this article aims to outline the incidence and consequences of nightmares in PTSD, illustrate how imagery rescripting could prove useful in their treatment, and investigate its clinical applications.